Fact and Fiction in Global Energy Policy : Fifteen Contentious Questions - Sovacool, Benjamin K. (Book collections on Project MUSE., 2016)
Energy sustainability and climate change are two of the greatest challenges facing humankind. Unraveling these complex and interconnected issues demands careful and objective assessment. Fact and Fiction in Global Energy Policy aims to change the prevailing discourse by examining fifteen core energy questions from a variety of perspectives, demonstrating how, for each of them, no clear-cut answer exists. Is industry the chief energy villain? Can we sustainably feed and fuel the planet at the same time? Is nuclear energy worth the risk? Should geoengineering be outlawed? Touching on pollution, climate mitigation and adaptation, energy efficiency, government intervention, and energy security, the authors explore interrelated concepts of law, philosophy, ethics, technology, economics, psychology, sociology, and public policy. This book offers a much-needed critical appraisal of the central energy technology and policy dilemmas of our time and the impact of these on multiple stakeholders.